Numerical study of heat transfer enhancement of counter nanofluids flow in rectangular microchannel heat exchanger - Mohammed, H.A.; Bhaskaran, G.; Shuaib, N.H.; Saidur, Rahman (Elsevier, 2011)
This paper reports a numerical analysis of the performance of a counter-flow rectangular shaped microchannel heat exchanger (MCHE) using nanofluids as the working fluids. Finite volume method was used to solve the three-dimensional steady, laminar developing flow and conjugate heat transfer in aluminum MCHE. The nanofluids used were Ag, Al2O3, CuO, SiO2, and TiO2 and the performance was compared with water. The thermal, flow fields and performance of the MCHE were analyzed using different nanofluids, different Reynolds numbers and different nanoparticle concentrations. Temperature profile, heat transfer coefficient, pressure profile, and wall shear stress were obtained from the simulations and the performance was discussed in terms of heat transfer rate, pumping power, effectiveness, and performance index. Results indicated enhanced performance with the usage of nanofluids, and slight penalty in pressure drop. The increase in Reynolds number caused an increase in the heat transfer rate and a decrease in the overall bulk temperature of the cold fluid. The increase in nanoparticle concentration also yielded better performance at the expense of increased pressure drop.